Pemberdayaan Masyarakat Melalui Pelatihan Pembuatan Pupuk Organik Sebagai Salah Satu Solusi Pengolahan Sampah Di Desa Karangkepoh, Karanggede, Boyolali) - Lina Agustina; Siti Kartika Sari (Universitas Sebelas Maret, 2025)
Organic waste is waste that is mostly composed of organic compounds (plant residues, animals, or feces) this waste is easily decomposed by living bodies, especially microorganisms. Organic waste can be used as raw material for making organic fertilizer (liquid fertilizer or compost), where organic fertilizer can be used by farmers. The purpose of this service activity is to increase community understanding of waste processing and the community can try to use organic fertilizer as a substitute for chemical fertilizers. The activity was carried out with PKK mothers in Karangkepoh Village, Karanggede District, Boyolali. The method of implementation is by conducting socialization related to waste and its processing, then training in making liquid organic fertilizer from household waste. The results of this activity are (1) the Karangkepoh village community knows how to process organic waste (2) the community can utilize liquid organic fertilizer to be applied to plants around the house as a substitute for chemical fertilizers.